Glencoe literature : the reader's choice. Course 4 - Chin, Beverly Ann.; Wolfe, Denny; Copeland, Jeffrey; Dudzinski, Mary Ann.; Ray, William; Royster, Jacqueline Jones; Wilhelm, Jeffrey (New York : Glencoe/McGraw-Hill, 2002)
The short story; Nonfiction; Poetry; Drama; Epic; Science fiction and fantasy.
Keywords: American literature; Literature -- Collections